Double Guard: Detecting Intrusions in Multitier Internet Applications - Bachhav, Tilottama; Dhamane, Komal; Kapadnis, Trutiya; Wagh, Vaishali (International Journal of Computer Sciences and Engineering, 2025)
Today, net services and applications have become an indivisible part of our daily life. So as to suit during this increase in application and data quality, web services have rapt to a multi-tier design in which, web server runs the application front-end logic and knowledge area unit which are out sourced to information or digital computer. Double-Guard is associate IDS that model the network behavior of user sessions across every front-end net server and additionally the back-end information. By watching both web and consequent database requests, system is able to find out attacks that free-lance IDS wouldn’t be able to determine. This system have tendency to quantify the short comings of any multi-tier IDS in terms of coaching sessions and practically coverage. Double Guard is implemented using an Apache web server with MySQL and light-weight virtualization. Finally, using Double-Guard, system has a tendency to expose a large range of attacks.